Circadian and seasonal dynamics of hematological indexes of blood of animals in norm and at influence of heavy metals (Experimental biology, 2018)
In this paper, the circadian and seasonal dynamics of hematological blood indices of animals in norm and under the influence of heavy metals are considered. One of the basic principles of the ordering of living organisms is their temporal structure, manifested in the form of rhythmically changing physiological and biochemical processes. Blood as one of the most important systems of an organism, plays an important role in its activity. Therefore any impacts on body tissues affect structure and properties of blood. Considering the explained provisions, need from positions of daily and seasonal dynamics to find out the range of hematological indexes of adaptations of animals in various conditions of dwelling and cultivation at the accruing anthropogenic impact on natural ecosystems, and to investigate reaction of system of blood of animals to influence of ions of heavy metals, that is to reveal features of reaction of system of blood of animals to influence of ions of cadmium, lead, copper and hydrargyrum, and to set the most sensing parameters of blood which can serve as indicators of pollution of the environment heavy metals ripened.Key words: circadian dynamics, seasonal dynamics, blood, hematological indexes, heavy metals.